"Are You Safe at Home?": Clinician's Assessments for Intimate Partner Violence at the Initial Obstetric Visit. (February 2023) - Huang, Cecilia; Hill, Amber; Miller, Elizabeth; Soudi, Abdesalam; Flick, Diane; Buranosky, Raquel; Holland, Cynthia L.; Hawker, Lynn; Chang, Judy C.
Few studies have empirically examined patient–clinician conversations to assess how intimate partner violence (IPV) screening is performed. Our study sought to examine audio-recorded first obstetric encounters' IPV screening conversations to describe and categorize communication approaches and explore associations with patient disclosure. We analyzed 247 patient encounters with 47 providers. IPV screening occurred in 95% of visits: 57% used direct questions, 25% used indirect questions, 17% repeated IPV screening later in the visit, 11% framed questions with a reason for asking, and 10% described IPV types. Patients disclosed IPV in 71 (28.7%) visits. There were no associations between disclosure and any categories of IPV screening.